Therapeutic emergence of dissociated traumatic memories during psilocybin treatment for anorexia nervosa - Stephanie Knatz Peck; Timothy D. Brewerton; Hannah Fisher; Julie Trim; Samantha Shao; Nadav Liam Modlin; Jessie Kim; Daphna M. Finn; Walter H. Kaye (Journal of Eating Disorders)
Abstract Background Psychedelic treatment is a rapidly emerging therapeutic approach for a host of chronic, difficult to treat psychiatric disorders, including anorexia nervosa (AN). Trauma and its sequelae, such as dissociation, often contribute to comorbidity and treatment refractoriness. Aims In this report, we describe the therapeutic emergence of previously dissociated traumatic memories of sexual assault in 2 of 10 research participants with AN while receiving psilocybin treatment. Methods Ten female adults who met DSM-5 criteria for AN or pAN (partial remission) participated in an open pilot study evaluating the safety, tolerability and preliminary efficacy of psilocybin-assisted psychotherapy. Participants received a 25-mg dose of investigational drug COMP360, a proprietary pharmaceutical-grade synthetic psilocybin formulation developed by COMPASS Pathfinder Ltd. administered in conjunction with psychological support. Participants also received two integration therapy sessions on days 1 and 7 after dosing, and they were reassessed at 1 and 3 months. Participants were interviewed using a semi-structured interview to understand qualitative perspectives of treatment and its effect on AN. Results/Outcomes Both patients described in this report significantly benefited from the emergence and processing of previously dissociated information (dissociative amnesia), and both patients subsequently attained remission of their AN psychopathology at 3-month follow-up as determined by global scores on the Eating Disorder Examination Questionnaire (EDE-Q) and clinically meaningful weight gain. Conclusions/Interpretation PT may hold promise not only in the treatment of eating disorders but also trauma-related disorders, including PTSD and dissociative amnesia. Potential mechanisms of psilocybin’s facilitation of remembering and processing traumatic material is reviewed.